On the Application of Noiseless Steganography and Elliptic Curves Cryptography Digital Signature Algorithm Methods in Securing Text Messages - Juhari Juhari; Mohamad Febry Andrean (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2022)
Elliptic curve cryptography includes symmetric key cryptography systems that base their security on mathematical problems of elliptic curves. There are several ways that can be used to define the elliptic curve equation that depends on the infinite field used, one of which is the infinite field prima (  where ). Elliptic curve cryptography can be used for multiple protocol purposes, digital signatures, and encryption schemes.The purpose of this study is to determine the process of hiding encrypted messages using the Noiseless Steganography method  as well as the generation of private keys and public keys and the process of verifying the validity of the Elliptic Curves Cryptography Digital Signature Algorithm (ECDSA).  The result of this thesis is that a line graph is obtained that store or hides a message using the steganography method and a message authenticity from the process of key generation and verification of validity using the ECDSA method. By selecting three samples consisting of one test sample and two differentiating samples, a line graph,  an MD5 hash value, and a value at the point are obtained  different. Successively obtained values  to message “Matematika 2018”, “MATEMATIKA 2018”, and “2018 matematika” are and . The discussion in this thesis only covers the elliptic curves on prime finite field. So, for the next thesis, the next researcher can do a discussion about the elliptic curve on the finite field  or the application of elliptic curve cryptography and other steganographic methods